Higher Order Thingking Skill (HOTS) untuk Anak Sekolah Dasar dalam Pembelajaran IPA - Oki Sandra Agnesa; Nisa Juniar Anggraini; Aishya Shaharani (MISOOL: Jurnal Pendidikan Dasar, 2022)
This research is backgrounded by the ability of students' Higher Order Thinking Skills (HOTS) in solving science learning problems. Therefore, a learning model is needed to improve students' Higher Order Thinking Skills (HOTS) abilities. The Problem Based Learning (PBL) model is a model that is very possible to be able to develop HOTS. Participants are trained to be able to design science learning based on the PBL model so that learning objectives related to the development of HOTS for students are achieved properly. The PBL model has learning stages in the form of 1) the orientation of the educated to the problem; 2) organizing learners to learn; 3) guiding individual or group investigations; 4) develop and present the work; and 5) analyze and evaluate problem solving. Therefore, the PBL model can help develop higher order thinking skills in science learning in elementary schools